Curricular Culture in PhD by Design: Perspectives Gained from the Aarhus School of Architecture. Issue 1 (9th December 2021) - Erckrath, Charlotte; Kaps, Vera; Andersson, Cecilie
Research by Design has grown in relevance in the field of architecture over the last decades, addressing research problems that are located at the core of design practice. This design research essay investigates European PhD by Design programmes in architectural schools from a curricular perspective. Through an evaluation of in-depth interviews, it opens up larger discussions on Research by Design by drawing upon the practical experience of PhD students, supervisors and the programme leader at the Aarhus School of Architecture. Based on the perspectives of situatedness, mindset and competency, the essay discusses the PhD programme as a curricular culture in which the research process unfolds. The term 'curricular culture' refers to the idea of cultivating the framework or space of emergence within which the PhD and its process of navigating the unknown takes place. The essay discusses how infrastructures and situated conversations within the framework of the Aarhus School and its wider network establish a dynamic and engaged research environment that is strongly connected to the school's specific identity.